Nanoscale metal–organic frameworks as photosensitizers and nanocarriers in photodynamic therapy - Matlou, Gauta Gold; Abrahamse, Heidi (Frontiers in Chemistry, 2022)
Photodynamic therapy (PDT) is a new therapeutic system for cancer treatment that is less invasive and offers greater selectivity than chemotherapy, surgery, and radiation therapy. PDT employs irradiation light of known wavelength to excite a photosensitizer (PS) agent that undergoes photochemical reactions to release cytotoxic reactive oxygen species (ROS) that could trigger apoptosis or necrosis-induced cell death in tumor tissue. Nanoscale metal–organic frameworks (NMOFs) have unique structural advantages such as high porosity, large surface area, and tunable compositions that have attracted attention toward their use as photosensitizers or nanocarriers in PDT. They can be tailored for specific drug loading, targeting and release, hypoxia resistance, and with photoactive properties for efficient response to optical stimuli that enhance the efficacy of PDT. In this review, an overview of the basic chemistry of NMOFs, their design and use as photosensitizers in PDT, and as nanocarriers in synergistic therapies is presented. The review also discusses the morphology and size of NMOFs and their ability to improve photosensitizing properties and localize within a targeted tissue for effective and selective cancer cell death over healthy cells. Furthermore, targeting strategies that improve the overall PDT efficacy through stimulus-activated release and sub-cellular internalization are outlined with relevance to in vitro and in vivo studies from recent years.